Functional anatomy and topographical organization of the frontotemporal arcuate fasciculus - Gianpaolo Antonio Basile; Victor Nozais; Angelo Quartarone; Andreina Giustiniani; Augusto Ielo; Antonio Cerasa; Demetrio Milardi; Majd Abdallah; Michel Thiebaut de Schotten; Stephanie J. Forkel; Alberto Cacciola (Communications Biology)
Abstract Traditionally, the frontotemporal arcuate fasciculus (AF) is viewed as a single entity in anatomo-clinical models. However, it is unclear if distinct cortical origin and termination patterns within this bundle correspond to specific language functions. We use track-weighted dynamic functional connectivity, a hybrid imaging technique, to study the AF structure and function in two distinct datasets of healthy subjects. Here we show that the AF can be subdivided based on dynamic changes in functional connectivity at the streamline endpoints. An unsupervised parcellation algorithm reveals spatially segregated subunits, which are then functionally quantified through meta-analysis. This approach identifies three distinct clusters within the AF - ventral, middle, and dorsal frontotemporal AF - each linked to different frontal and temporal termination regions and likely involved in various language production and comprehension aspects. Our findings may have relevant implications for the understanding of the functional anatomy of the AF as well as its contribution to linguistic and non-linguistic functions.